LOKUS KENDALI DAN KUALITAS HIDUP LANSIA DENGAN HIPERTENSI - Hariati, Hariati; Girsang, Rostiodertina; Sitorus, Friska Ernita; Zuliawati, Zuliawati; Riyantoi, Riyanto (Fakultas Keperawatan Institut Kesehatan Deli Husada, 2024)
Hypertension is a disease that many elderly people suffer from, who are vulnerable to experiencing a decrease in quality of life due to decreased organ function. Quality of life is influenced by locus of control. The aim of this study was to determine the relationship between locus of control and the quality of life of elderly people with hypertension. Correlation research design. Population 426 elderly, sample 209 elderly. Statistical tests use Pearson correlation. The results show that there is a relationship between locus of control and the quality of life of hypertensive elderly people, p=0.001 (P<0.05). Observation of the locus of control is very important to improve the quality of life of the elderly in order to improve the welfare of the elderly in old age.